Estrogen and Progesterone Receptor Status in Breast Cancer-Its Relation to Age, Axillary Lymph Node Status, Tumour’s Maximum Dimension and Grade of Tumour - Hasanuzzaman, Md; Rahman, Md Mizanur; lslam, Md Johirul; Haque, Md Ashraf UI; Rahman, Md Setabur; Rahman, Md Mafizur (Journal of Surgical Sciences, 2019)
Background: Carcinoma of the breast is one of the most common malignancies of women in our country. The current study was conducted with the objective of assessing Oestrogen receptor (ER) and progesterone receptor (PR) status of carcinoma breast for correlation with age of the patient, tumor dimension, axillary lymph node metastasis and histologic grade. Methodology: One hundred and nineteen female breast cancer patients operated at the surgical oncology department of National Institute of Cancer Research & Hospital were selected by non-probability sampling method and operated specimens were sent for immunohistochemical study of the Oestrogen receptor and progesterone receptors. Statistical analysis was conducted using SPSS version 12 for Windows software. P-value 0.05 or less was considered as significant. Result: Mean age of the patients was 41.64 years (95 % Cl 39.8, 43.5). About 87% of the ER+ and PR+ patients had tumour dimension < 5 cm. The predominant morphology was infiltrating duct cell carcinoma. Out of 66 ER+ cases 63 were the patients of Infiltrating duct cell carcinoma and in 63 PR+ cases 60 were the patients of same histological type. The majority of the cases presented as grade II (59.1%) followed by grade Ill (33.9%). Sixty percent patients had axillary lymph node metastasis. Majority of the patients (51.3%) expressed both the receptors in their breast tissue while around 43% of the patients did not show any receptor. Conclusion: ER and PR expression in breast cancers in the current study was found to be comparable to published national and international data. Assessment of prognostic markers for the clinical management of breast cancer patients is strongly advocated to provide best therapeutic options. Journal of Surgical Sciences (2013) Vol. 17 (2) : 84-88